Strategi Pembelajaran Guru Agama Hindu Dalam Menumbuhkembangkan Karakter Disiplin Siswa di SMA Dwijendra Denpasar - Cahyani, Ayu Indah; Suwedawati, Gusti Ayu Kadek Arni; Prawita, Wayan Cahya (Jayapangus Press, 2023)
Character education is one of the leading indicators for producing human beings who have character and act reasonably in a formal environment. Education can also be understood as human interaction activities between teachers and students to achieve educational goals. This study aims to explain the personality developed by educators in forming personality, especially the disciplinary character of students, starting from lesson planning, learning implementation, obstacles encountered, and efforts made by SMA Dwijendra Denpasar teachers. This research is qualitative descriptive research, where data is obtained through observation, interviews, documentation, and literature study. The collected data were analyzed using data reduction procedures, data presentation, and qualitative descriptions by conclusion. The results of the study show that the learning strategies of Hindu teachers in developing the discipline of students at SMA Dwijendra Denpasar are (1) The learning plans for Hindu teachers at SMA Dwijendra Denpasar include learning curriculum, syllabus, and learning implementation plans (RPP). (2) Classroom learning in developing the character of student discipline (preparatory activities, core activities, final learning activities) and strategies used in learning Hindu religious education (Exposition learning strategy and Cooperative Strategy type group investigation) methods used to carry out Hindu religious learning in the development of student discipline personalities. Learning methods include (habituation, demonstration, and learning task method). (3) The obstacles and efforts of Hindu religious teachers in growing and developing disciplinary actions for students include disciplinary violations (students are late for school, how to dress/uniform, not picket in class, do not do assignments from the teacher). Efforts to overcome these obstacles involve applying student discipline, excellence, motivation, and appreciation.